P265 The clinical utility of biomarkers associated with inflammation and endothelial dysfunction in CTEPH. (12th November 2015) - Hadinnapola, C; Southwood, M; Hernandez-Sanchez, J; Sheares, K; Preston, S; Jenkins, D; Morrell, N; Toshner, M; Pepke-Zaba, J
Abstract : Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare form of pulmonary hypertension. Inflammation, defective angiogenesis and endothelial dysfunction have been implicated in its pathogenesis. We assessed the prognostic utility of biomarkers, related to these processes, in pulmonary endarterectomy (PEA) assessment. Methods: 80 patients with CTEPH had serum samples taken immediately prior to PEA and a subset (n = 54) also at follow-up after PEA. 20 healthy volunteers and 20 patients with idiopathic pulmonary arterial hypertension (IPAH) served as controls. Samples were processed on a custom-designed Luminex multiplex array. Biomarker levels were correlated to haemodynamics and functional assessments. Material removed during PEA and explanted lungs of CTEPH and IPAH patients were additionally analysed using immunostaining. Results: Compared to healthy controls Pre PEA samples showed increases in interleukin (IL)-8, -10, tumour necrosis factor α (TNFα), high sensitivity C-reactive protein (hsCRP) and angiopoietin 2 (Ang2). Vascular endothelial growth factor (VEGFc) was higher in healthy controls. Following PEA (6.00 ± 1.83 months), improvements in haemodynamics and six-minute walk distance were observed compared to baseline (Table 1 ). Additionally, there were decreases in Ang2 and Endoglin. Preoperative Ang2 levels were independently associated with baseline pulmonary vascular resistance (PVR) with multiple linear regression (p < 0.0001). A similar association was found in IPAH subjects (p < 0.05). Ang2 expression was demonstrated in the endothelium of distal pulmonary arteries in both IPAH and CTEPH notably in areas of small vessel vasculopathy and in neovessels found in the PEA specimens. The clinical utility in predicting small vessel vasculopathy and residual CTEPH post-PEA surgery was assessed using a cross validation approach. Baseline Ang2 was a necessary component of the best multiple linear model for predicting PVR at follow up (along with baseline PVR, WHO class, age and the use of PAH targeted therapy) r 2 = 0.39, q 2 = 0.35. Conclusion: We found only modest increases in any marker of inflammation in CTEPH, they were not normalised by PEA or correlated to disease severity. By comparison Ang2 correlated with haemodynamics and has utility in predicting postoperative outcomes.